Nurses' perceptions of patient participation in the myocardial infarction pathway. Issue 5 (15th June 2020) - Bårdsgjerde, Elise Kvalsund; Landstad, Bodil J.; Hole, Torstein; Nylenna, Magne; Gjeilo, Kari Hanne; Kvangarsnes, Marit
Abstract: Aim: To explore nurses' perceptions of patient participation in different phases of the myocardial infarction pathway. Design: Qualitative design with a hermeneutical approach. Methods: Five focus groups were conducted at two hospitals, one with and one without percutaneous coronary intervention facilities, between February–November 2018. Participants were recruited through purposive sampling. Twenty‐two nurses experienced in cardiac care participated. The analysis had a hermeneutical approach. Results: The findings revealed nurses' perceptions of patient participation in different phases of the myocardial infarction pathway. Four themes were identified: (a) variation between paternalism and autonomy in the acute phase; (b) individualization of dialogue and patient participation during treatment; (c) lack of coherence in the pathway hinders patient participation at discharge; and (d) cardiac rehabilitation promotes patients' autonomous decisions in lifestyle changes.